2016
DOI: 10.1002/cmdc.201600213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Iodoglucoazomycin (I‐GAZ), an Azomycin–Glucose Adduct with Putative Applications in Diagnostic Imaging and Radiotherapy of Hypoxic Tumors

Abstract: Iodoglucoazomycin (I‐GAZ; N‐(2‐iodo‐3‐(6‐O‐glucosyl)propyl)‐2‐nitroimidazole), a non‐glycosidic nitroimidazole–6‐O‐glucose adduct, was synthesized, radioiodinated, and evaluated as a substrate of glucose transporter 1 (GLUT1) for radiotheranostic (therapy+diagnostic) management of hypoxic tumors. Nucleophilic iodination of the nosylate synthon of I‐GAZ followed by deprotection afforded I‐GAZ in 74 % overall yield. I‐GAZ was radioiodinated via ‘exchange’ labeling using [123/131I]iodide (50–70 % RCY) and then pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This prevalence of hypertension was significantly higher among participants from KASS (15.2%), compared to KOSS (5.6%), and BOSS (3.7%; P <0.001). Similar but higher prevalence of hypertension among adolescents was found in a study by Kumar et al [18]. On the other hand, another study by Tadesse and Alemu [19] in Ethiopia found a slightly lower prevalence of hypertension (7.7%) among adolescents.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This prevalence of hypertension was significantly higher among participants from KASS (15.2%), compared to KOSS (5.6%), and BOSS (3.7%; P <0.001). Similar but higher prevalence of hypertension among adolescents was found in a study by Kumar et al [18]. On the other hand, another study by Tadesse and Alemu [19] in Ethiopia found a slightly lower prevalence of hypertension (7.7%) among adolescents.…”
Section: Discussionsupporting
confidence: 82%
“…A cross-sectional study was carried out on adolescent SHS students aged [13][14][15][16][17][18][19]…”
Section: Study Design and Eligibilitymentioning
confidence: 99%
“…Few articles have been found on sand recycling, in the scientific literature (Bradley et al, 2018;Kristula, Rogers, Hogan, & Sabo, 2005;Kumar et al, 2016;Zdanowicz, Shelford, Tucker, Weary, & Keyserlingk, 2004), and none of them evaluate its economic viability. Thus, the present study proposes to examine the economic viability of implementing the necessary infrastructure for the recycling of bedding sand from a free-stall facility in a milk production system in southern Minas Gerais, Brazil.…”
Section: Introductionmentioning
confidence: 99%